Peer influence and its impact on behavior among South Indian adolescents: A descriptive cross-sectional study - Jisha M. Alexander; Renjulal Yesodharan; Malathi G. Nayak (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Peer influence, the development of attitudes, and behavioral changes are some of the phenomenal changes that happen in adolescence. MATERIALS AND METHODS: A descriptive cross-sectional study was undertaken to find out the association between peer influence and behavior among 355 adolescents within the age group of 16 to 18 years, randomly chosen from Pre-university schools of Udupi district, Karnataka using the Peer Influence Scale (PIS) and Strengths and Difficulties Questionnaire (SDQ). RESULT: The results indicate that their peers highly influenced 43.9% of the participants. Meanwhile, 23.1% and 7.9% of adolescents who participated in the survey showed borderline and abnormal behavior, respectively. The association between peer influence and behaviour was assessed using the Chi-square test; the results (χ2=14.545, P = 0.001) revealed that peers highly influence adolescent behavior and change adolescent conduct significantly. CONCLUSION: Adolescents should be aware of the accepted and non-accepted behaviors in society and be wise in choosing the right peers who later influence their behavior. Parents need to check the conduct of their children and guide them in developing their identity.